2023
DOI: 10.1039/d3sc03117a
|View full text |Cite
|
Sign up to set email alerts
|

Selective thiazoline peptide cyclisation compatible with mRNA display and efficient synthesis

Minglong Liu,
Richard Morewood,
Ryoji Yoshisada
et al.

Abstract: Peptide display technologies are a powerful method for discovery of new bioactive sequences, but linear sequences are often very unstable in a biological setting. Macrocyclisation of such peptides is beneficial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…To assess whether atropisomeric quinolines could be introduced within ribosomal peptides, we first confirmed that Friedländer reaction of peptide 28 with (2-aminophenyl)(o-tolyl)methanone (26) in AcOH at 60 °C for 48 h produced the expected product 29 as a roughly 41:59 mixture of atropisomeric products, as determined by 1 H NMR (Fig. 4a).…”
Section: Friedländer Reactions Of β-Keto Amides Generate Stable Atrop...mentioning
confidence: 76%
See 2 more Smart Citations
“…To assess whether atropisomeric quinolines could be introduced within ribosomal peptides, we first confirmed that Friedländer reaction of peptide 28 with (2-aminophenyl)(o-tolyl)methanone (26) in AcOH at 60 °C for 48 h produced the expected product 29 as a roughly 41:59 mixture of atropisomeric products, as determined by 1 H NMR (Fig. 4a).…”
Section: Friedländer Reactions Of β-Keto Amides Generate Stable Atrop...mentioning
confidence: 76%
“…Indeed, Lewis acids such as the chloride salts of Ce(III) 70 and Fe(III) 71 as well as the triflate salts of Yb(III) 72 , Y(III) 73 , and Zn(II) 74 , can promote Friedländer reactions of β-ketoesters 48 . To evaluate if they could improve atropisomer-forming reactions of β-keto amide 2-P1, we screened their effect (at 20 mol%) on the Friedländer reaction of dipeptide 5 and (2-aminophenyl)(o-tolyl)methanone (26) to generate the quinoline 27 (Supplementary Fig. 9 and Supplementary Table 3).…”
Section: Lewis Acid Catalysis Of Post-translational Friedländer React...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to in vivo genetic code expansion, the FIT system is able to easily translate side chain-functionalized l -AA derivatives. Generally, tRNA AsnE2 is used, as EF-Tu affinity is not an issue, though for some bulkier npMs the optimized T stem of tRNA GluE2 may be necessary (refs , , , , , , , , , and ). In a similar manner to RaPID, the PURE system has also been combined with Mj TyrRS/tRNA opt CUA pairs for mRNA display selections by Iskandar and co-workers in 2023. , As the cotranslational incorporation of l -AA derivatives is more efficient than backbone-modifying npMs and has been extensively reviewed elsewhere, it will not be discussed in detail. ,, However, these npMs are nevertheless important and are often used in RaPID selections for their beneficial side chains.…”
Section: Applications Of Polypeptides Containing Ribosomally Translat...mentioning
confidence: 99%
“…Jongkees, Nitsche & co-workers recently reported a similar strategy where they combined the selective reactivity of N-terminal cysteine and non-N-terminal cysteine to construct bicyclic peptide libraries. 211 …”
Section: Strategies For Peptide Macrocyclisationmentioning
confidence: 99%